2019
DOI: 10.18410/jebmh/2019/203
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Status of Vitamin D3 Level Among Patients Diagnosed as Case of Hypothyroidism in a Medical College, Tripura

Abstract: BACKGROUND Vitamin D3 receptors are present in different body tissues like myocardium, pancreas, thyroid gland etc. Since both Vitamin D3 and thyroid hormones act via steroid receptors, any alteration in the level of Vitamin D3 is likely to increase problems associated with hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The present study showed decreased mean vitamin D levels in the study group, which were significantly (p<0.01) lower than those in the control group. This finding has been supported by different researchers from different countries [22,23,27,28,34,37,38]. Furthermore, there were no significant differences in vitamin D between the different age groups in the study group.…”
Section: Vitamin Dsupporting
confidence: 73%
See 1 more Smart Citation
“…The present study showed decreased mean vitamin D levels in the study group, which were significantly (p<0.01) lower than those in the control group. This finding has been supported by different researchers from different countries [22,23,27,28,34,37,38]. Furthermore, there were no significant differences in vitamin D between the different age groups in the study group.…”
Section: Vitamin Dsupporting
confidence: 73%
“…Furthermore, serum vitamin D decreased when the TSH level increased and vice versa. Various researchers from different countries have observed a similar correlation between vitamin D and TSH [25,27,37]. These results suggested that there may be a significant association between vitamin D deficiency and hypothyroidism.…”
Section: Correlation Between the Tsh Vitamin D And Ironmentioning
confidence: 53%
“…Islam et al 38 measured vitamin D and TSH for 45 females (hypothyroid individuals aged 25-65 years). Vitamin D decreased significantly in hypothyroid individuals (19.2 ± 1.40 ng/mL) compared to the control group (28.4 ± 1.36 ng/mL, P < 0.001).…”
Section: Studies About the Relation Of Hypothyroidism With Vitamin Dmentioning
confidence: 99%